Association of Abnormal Pap Smear with Occult Cervical Stromal Invasion in Patients with Endometrial Cancer - Khumthong, Kewalin (Asian Pac J Cancer Prev, 2019)
OBJECTIVE: The purpose of this study was to determine the association between abnormal preoperative Pap smear results and occult cervical stromal invasion in endometrial cancer patients. METHODS: Medical records were reviewed of patients with endometrial cancer who had undergone surgical staging at Srinagarind Hospital. Patients with gross cervical involvement, with an unsatisfactory Pap smear, without available Pap smear results, with no cervical intraepithelial lesion/invasive cervical cancer, or who had previously undergone pelvic radiation therapy were excluded. The patients were assigned to one of two groups according their Pap smear results (negative and epithelial cell abnormalities). Logistic regression was used to determine the independent association between an abnormal Pap smear and the risk of cervical stromal invasion. RESULTS: All cervical smears in this study were performed as conventional Pap smears. Smears were abnormal in 50 (21.0%) of the 238 patients enrolled and normal in the remaining 188 (79.0%). The types of Pap smear abnormalities included adenocarcinoma (n=22); atypical endometrial cells (n=2); atypical glandular cells (n=17); high-grade squamous intraepithelial lesions (n=4); atypical squamous cells, cannot exclude high-grade squamous intraepithelial lesions (n=2); and atypical squamous cells of undetermined significance (n=3). After controlling for type of endometrial cancer, abnormal Pap smear results were found to be a significant independent factor that indicated cervical stromal invasion (adjusted OR 2.65; 95% CI 1.35 to 5.21). CONCLUSION: Endometrial cancer patients with abnormal Pap smears were strongly and independently associated with histopathologically diagnosed cervical stromal invasion.